Wage Growth, Landholding, and Mechanization in Agriculture : Evidence from Indonesia - Yamauchi, Futoshi (World Bank, Washington, DC, 2014)
This paper uses farm panel data from Indonesia to examine dynamic patterns of land use, capital investments, and wages in agriculture. The empirical analysis shows that an increase in real wages has induced the substitution of labor by machines among relatively large farmers. Large farmers tend to increase the scale of operation by renting in more land when real wages increase. Machines and land are complementary if the scale of operation is greater than a threshold size. In contrast, such a dynamic change was not observed among relatively small holders, which implies a divergence in the movement of the production frontier between Java and off-Java regions given that the majority of small farmers are concentrated in Java.